ASPEK KLINIS DAN EPIDEMIOLOGIS PENDERITA VERTIGO - Jusuf, Muhammad Isman (Sainstek, 2008)
Vertigo is one of the most complaints that endorse patients to visit a physician. Vertigo can be classified into central and peripheral type. Till present there is no gold standard for vertigo examination. Anamnesis and the severity of the complaint are often used to establish the diagnosis of vertigo.